Cover Crop Biomass Removal Rates to Optimize Livestock Production and Soil Health in No-tillage Dryland Cropping Systems - Logan M. Simon; Augustine K. Obour; Zachariah C. Carson; Frank Weber; Stacie Minson; Craig Dinkel (Kansas Agricultural Experiment Station Research Reports, 2024)
Grazing cover crops (CCs) could provide an economic benefit to offset potential lost revenue when grain crop yields are decreased after CCs in dry years. However, there is limited guidance on the optimum biomass removal rate that balances soil health and grazing goals. An on-farm study was established in fall 2022 on a 50-a producer field in Russell Co., KS, to investigate the effects of CC biomass removal rates with cattle grazing on soil health parameters and grain crop yields, and profitability in no-till (NT) dryland cropping systems. The study design was a randomized complete block with three treatments and four replications. The treatments included ungrazed CCs, “take-half-leave-half” (T-H-L-H, 50% biomass removal), and “graze-out” (G-O, 90% biomass removal). Results showed that T-H-L-H and G-O significantly reduced CC residue amount and height compared to ungrazed CCs but maintained residue cover on the soil surface similar to ungrazed CCs. Cover crop management had no significant effect on soil organic carbon, particulate organic matter, nitrate-N, or P concentrations. However, T-H-L-H somewhat increased soil bulk density compared to ungrazed CCs, though both were similar to G-O. Soil penetration resistance, wind-erodible fraction, mean weight diameter of water stable aggregates, time-to-runoff, and subsequent grain sorghum yield were unaffected by CC management. These results suggest that farmers and ranchers may be able to graze CCs at greater intensities than T-H-L-H to maximize livestock gains while maintaining soil health. This approach could increase adoption of CCs and benefit water quality protection and improvement efforts in reaching the goals of the approved 9 Element Watershed Plan through the Kansas Department of Health and Environment and Environmental Protection Agency. However, these observations were made in a 1-year study and under exceptional drought conditions, so further investigation will be necessary under conditions of average or above average precipitation when wet soils may be more susceptible to degradation by cattle hoof traffic.
Keywords: Cover crops; biomass; grazing; soil health